Correlation Between Insulin Resistance Indices And Endometrial Thickness To Predict Metabolic Syndrome & Ovulatory Dysfunction In Phenotypes Of Polycystic Ovarian Syndrome In South Indian Population - S, Lavanya; V, Dr. Sureka Varalakshmi (Migration Letters, 2024)
Study objective: Tocorrelate between Insulin Resistance Indices and Endometrial Thickness to predict Metabolic syndrome & ovulatory dysfunction in Phenotypes of Polycystic Ovarian Syndrome in south Indian population. Methods: Forty reproductive-aged women (18–35 years old) who met the Rotterdam criteria for PCOS were enrolled in the Gynaecology outpatient department at our hospital were included in the study. The subjects were categorised based on the Rotterdam criteria into 4 phenotype groups. For all study participants, endometrial thickness and the insulin resistance indices was calculated using the biochemical parameters. The data was analyzed by Pearson’s correlation coefficient for relationship between variables. Statistical analyses were performed with the help of SPSS software. For all statistical analyses the p value was significant when p <0.05. Results:Correlation between endometrial thickness & insulin resistance indices in PCOS Phenotype A, phenotype -C & phenotype-D samples: The indices VAI, LAP, FAI, TyG& SPISE showed negative correlation with endometrial thickness. In PCOS Phenotype B samples: The indices LAP, FAI & SPISE showed negative correlation whereas the indices VAI &TyG showed positive correlation with endometrial thickness with the Pearson’s correlation coefficient value(R) of -0.99 with p value of <0.01 & value(R) of -0.98 p value of <0.02 respectively showing statistically significant. Conclusion:In PCOS phenotypes, especially with PCOS Phenotype B there is a substantial correlation between the insulin resistance indices & endometrial thickness. They are simple and affordable markers that have a good sensitivity and specificity for the diagnosis of metabolic syndrome & ovulatory.